The prevalence, anatomic locations and characteristics of the odontomas using panoramic radiographs - Hakan Avsever; Hakan Kurt; Tolga Berkay Suer; Hilal Peker Ozturk; Bulent Piskin (Wolters Kluwer Medknow Publications, 2015)
Objectives: Odontomas are the most common variety of odontogenic tumors and derived from differentiated epithelial and mesenchymal cells. The purpose of this study is to evaluate the prevalence, types and localization of the odontomas in Turkish patients. Materials and Methods: This was a retrospective study of panoramic images that were taken between April 2011 and January 2014 in the Department of Dentomaxillofacial Radiology, Gulhane Military Medical Academy (GATA), Turkey. A total of 14,250 panoramic images were evaluated by an experienced dentomaxillofacial radiology specialist. The clinicopathologic features of odontomas such as, anatomic location, distribution in gender, age of the patients and the incidence of the odontomas were assessed. Results: A total of 22 odontomas in 20 patients (11 females; 9 males) (0.14%) were found of the 14,250 patients` panoramic view. About 36.4% of the lesions were complex odontomas and 63.6% were diagnosed as compound odontomas. About 18.2% of all cases were in the maxilla and 81.8% in the mandible. The anterior portion of mandible was found the most common location (40.9%) in this study. Conclusions: According to the result of this study, the compound types of the odontomas are more common than complex odontomas and the anterior mandible is the most affected site. It was noted that even though odontomas are the most common variety of odontogenic tumors, they rarely occur.